Dopamine Transporter Knockout Rats Show Impaired Wellbeing in a Multimodal Severity Assessment Approach - Mallien, Anne Stephanie; Becker, Laura; Pfeiffer, Natascha; Terraneo, Federica; Hahn, Melissa; Middelman, Anthonieke; Palme, Rupert; Creutzberg, Kerstin Camile; Begni, Veronica; Riva, Marco Andrea; Leo, Damiana; Potschka, Heidrun; et al. (Frontiers in Behavioral Neuroscience, 2022)
In preclinical psychiatry research, animals are central to modeling and understanding biological mechanisms of behavior and psychiatric disorders. We here present the first multimodal severity assessment of a genetically modified rat strain used in psychiatric research, lacking the dopamine transporter (DAT) gene and showing endophenotypes of several dopamine-associated disorders. Absence of the DAT leads to high extracellular dopamine (DA) levels and has been associated with locomotor hyperactivity, compulsive behaviors and stereotypies in the past. The German Animal Welfare Law, which is based on the EU Directive (2010/63/EU), requires a prospective severity assessment for every animal experiment, depending on the extent of the expected degree of pain, suffering, distress or lasting harm that the animals will experience. This should consider all procedures but also the impact of the genotype on the phenotype. Therefore, we examined multiple parameters indicating animal welfare, like burrowing behavior, social interaction, saccharin preference, baseline stress hormone levels and nesting behavior. Additionally, a footprint analysis was performed and home cage activity was analyzed for a more detailed characterization of locomotion. DAT KO rats demonstrated reduced burrowing, social interaction and saccharin preference. We also found pronounced stereotypies and alterations in the gait analysis in DAT KO rats. Moreover, we confirmed the hyperactivity and the impaired sensorimotor gating mechanisms to assure that our rats are exhibiting the correct phenotype. In conclusion, we provide evidence that DAT KO rats show alterations in natural behavior patterns and deduce that the marked stereotypies are a sign for coping difficulties, both indicating a negative influence of the genotype on wellbeing. We suggest to assess further rat models in an objectified severity assessment as previously done in mice to create a relative severity assessment based on scientific evidence. Until then, we propose the classification of homozygous DAT KO rats as “moderate” in accordance with the criteria of the EU directive 2010/63.